ANALISIS EFISIENSI SALURAN PEMASARAN HASIL TAMBAK UDANG TRADISIONAL (Studi Pada Tambak Udang Tradisional di Desa Labuhan Alas) - K Kurniawansyah; Ishak Rahman; S Saupiat (Fakultas Ekonomi dan Manajemen, 2021)
This study aims to know the shrimp marketing system of traditional ponds in Labuhan Alas Village, Alas District, Sumbawa District, margins of each shrimp marketing institution, shrimp marketing channel and to know efficiency of shrimp marketing in each marketing method in Labuhan Alas Village. , Alas Sub-District, Sumbawa District. The type of this study was descriptive study used quantitative and qualitative data. Data was collected through interviews. Analysis of the data used was descriptive statistics using the formula to calculate margins and the efficiency of each marketing agency and marketing channel. The result of study showed that shrimp marketing system in Labuhan Alas Village, Alas Sub-District, Sumbawa District consisted of two marketing channels, namely: (1) fisherman ? collector ? retailer, (2) fisherman ? collector ? distributor/agent trader ? retailer. In marketing channel I, collectors had margin of Rp. 6.300/Kg and it was the highest margin in this channel, while in retailers, it was Rp. 2.000/Kg. In Marketing Channel II, collectors had the highest margin of Rp. 6.3000/Kg, dealers/agents had margin of Rp. 6.000/Kg, then retailers had margin of Rp. 6.000/Kg. The most efficient marketing channel was marketing channel I with percentage of marketing efficiency of 5,73%, it was because there were few marketing institutions and the costs incurred in marketing channel I was smaller than other marketing channels with the highest share margin of 84,91%.